Tel Aviv-Yafo. Zum Problem des Einflusses heterogener Einwanderungsgruppen auf Stadtstruktur und Stadtentwicklung - Ruppert, Helmut (ERDKUNDE, 1974)
The waves of Jewish immigration into Pales tine and Israel have been characterised by their distinctive composition of regards areas of origin. From the cultural, economic and social heterogeneity of the Jewish immigrants, an influence on spatial group behaviour would be expected. The temporal-spatial impact of the immigrant groups was investigated using the example of the structure and development of the city of Tel Aviv-Yafo. Starting from the traditional elements of the oriental levantine city of Jaffa, the influence of Russian and Polish emigrants on the founding and structure of Tel Aviv in the years 1909-1931 is described. The waves of central European Jewish immigrants into Palestine in the years 1932 1938 gave dynamic impetus to the economic and cultural development of the city. Vigorous growth in the tertiary sector made Tel Aviv into the main urban centre of Pales tine. The mass immigration between 1948 and 1953, with an emphasis on Bulgarian and Rumanian Jews and Jews from oriental countries, brought an educationally and economically weaker population to Tel Aviv, which made a distinctive contribution to the structure of the southern parts of the city through its often traditional way of life. The most recent development is characterised by the strong economic influence of North American Jews. The influence exerted on urban spatial structure exerted by the material position, the cultural tradition and the general way of life of immigrants from particular areas of origin was studied by field investigation in the Hatikva Quarter and in Yafo. An increasingly important question concerns the forces which are loosening ethnic bonds. The spatial pattern created in housing, economic and cultural activity by the old way of life is changed by these forces and a spatial regrouping takes place along lines of wealth and property ownership. The tertiary sector has a special significance as a formative element in the development of a modern western society. In essence, however, the influence of ethnic origins can be recognised in the functional composition of the city. In addition to the specific structure of residential areas and the handicraft and industrial areas, the central business districts of Tel Aviv-Yafo must be seen in relation to their adaptation to new immigrant groups and their economic needs.